Development of a HPLC Method for Analysis of a Combination of Clofazimine, Isoniazid, Pyrazinamide, and Rifampicin Incorporated into a Dermal Self-Double-Emulsifying Drug Delivery System - Daniélle van Staden; Richard K. Haynes; Frank Van der Kooy; Joe M. Viljoen (Methods and Protocols, 2023)
We describe the development and validation of a new high performance liquid chromatography (HPLC) method for analysis of a combination of the first-line anti-tubercular drugs isoniazid, pyrazinamide, and rifampicin together with clofazimine. This is a unique challenge since clofazimine and rifampicin are relatively highly lipophilic drugs, whereas isoniazid and pyrazinamide are considerably more hydrophilic. Thus, clear separation of peaks and quantification of four individual drugs can present difficulties during the development of an analytical method. Detection was established at two wavelengths—254 nm for isoniazid and pyrazinamide and 320 nm for clofazimine and rifampicin. Gradient elution was employed using 0.1% aqueous formic acid (A) and acetonitrile (B); clear separation of the four drugs was achieved within 10 min. A linear relationship was indicated by a correlation coefficient (r2) of 0.9999 for each anti-tubercular drug, respectively. The limit of detection (LOD) for the individual drugs was 0.70 µg/mL (isoniazid), 0.30 µg/mL (pyrazinamide), 0.20 µg/mL (rifampicin) and 0.20 µg/mL (clofazimine). Precision experiments rendered a mean recovery percentage of 101.25% (isoniazid), 98.70% (pyrazinamide), 99.68% (rifampicin) and 97.14% (clofazimine). This HPLC method was validated and is reliable, repeatable, and accurate for the purpose of conducting simultaneous HPLC analyses of the four anti-tubercular drugs.